Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: (a+b+c)^2 + a^2 + b^2 + c^2
= a^2 +b^2 +c^2 + 2ab + 2ac + 2bc + a^2 + b^2 + c^2
= (a^2 +2ab+ b^2) + (b^2 +2bc+ c^2) +(c^2 +2ac+ a^2 )
= (a+b)^2 +(b+c)^2 +(c+a)^2
\(\left(a^2+b^2+c^2\right)+a^2+b^2+c^2\)
\(=a^2+b^2+c^2+2ab+2bc+2ac+a^2+b^2+c^2\)
\(=\left(a+b\right)^2+\left(b+c\right)^2+\left(c+a\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
2(a-b)(c-b)+2(b-a)(c-a)+2(b-c)(a-c)
=2a^2+2b^2+2c^2-2bc-2ab-2ac
=a^2-2ac+c^2+a^2-2ab+b^2+b^2-2bc+c^2
=(a-c)^2+(a-b)^2+(b-c)^2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(a+b+c\right)^2+a^2+b^2+c^2\)
\(=a^2+b^2+c^2+2ab+2bc+2ca+a^2+b^2+c^2\)
\(=a^2+2ab+b^2+b^2+2bc+c^2+c^2+2ca+a^2\)
\(=\left(a+b\right)^2+\left(b+c\right)^2+\left(c+a\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
=a^2+b^2+c^2=2ab+2bc+2ca+a^2+b^2+c^2
=(a^2+2ab+b^2)+(b^2+2bc+c^2)+(c^2+2ca+c^2)
=(a+b)^2+(b+c)^2+(c+b)^2
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 2 :
a ) \(A=\left(a+b+c\right)^2+a^2+b^2+c^2\)
\(A=a^2+b^2+c^2+2ab+2ac+2bc+a^2+b^2+c^2\)
\(A=\left(a^2+2ab+b^2\right)+\left(a^2+2ac+c^2\right)+\left(b^2+2bc+c^2\right)\)
\(A=\left(a+b\right)^2+\left(a+c\right)^2+\left(b+c\right)^2\)
[(a−b)(c−b)+(b−a)(c−a)]+[(b−a)(c−a)+(b−c)(a−c)]+[(b−c)(a−c)+(a−b)(c−b)][(a−b)(c−b)+(b−a)(c−a)]+[(b−a)(c−a)+(b−c)(a−c)]+[(b−c)(a−c)+(a−b)(c−b)]
= [(a−b)(c−b−c+a)]+[(c−a)(b−a−b+c)]+[(b−c)(a−c−a+b)][(a−b)(c−b−c+a)]+[(c−a)(b−a−b+c)]+[(b−c)(a−c−a+b)]
= (a−b)2+(c−a)2+(b−c)2